Adapting sorghum and other millets to climate challenges: An integrated bibliometric and meta-analysis of global literature - V. Visha Kumari; Aniket Deo; Kaushik Bora; C.A. Rama Rao; B.M.K. Raju; M.A. Sarath Chandran; K. Sriram; V.K. Singh; Pramod K. Aggarwal (Journal of Agriculture and Food Research)
Sorghum and other millets, despite being known for their resilience, face significant agroclimatic challenges, including erratic rainfall, high temperatures, drought, dry spells and nutrient-poor soils. These crops, being significantly important in semi-arid and arid regions globally, invite more research focus. Given the lack of structured synthesis of climate adaptation research for sorghum and other millets, we conducted a systematic literature review to identify trends and associations in research with bibliometric analysis and estimate effectiveness of various climate adaptation options with meta-analysis. It is evident from our results that there's a shift in research trends towards data-driven techniques, such as machine learning, bio-fertilizers like biochar, nutrition-related areas like biofortification, and climatic hazard like waterlogging in sorghum and other millets literature. In terms of climatic hazards, drought and dry spells are the most studied phenomena. Our findings from meta-analysis show that agricultural adaptation options like stress tolerant varieties, tillage practices, and multiple adaptation options with tillage and integrated nutrient management show, 53 %, 52 % and 38 % mean yield improvement, respectively. Moreover, we examined the relationship of yield improvement with critical environmental factors such as soil, rainfall and temperature. This study provides a macroscopic overview of accumulated knowledge and underscores the need for continued and targeted interventions to enhance climate resilience of sorghum and other millets.